Isolation of Lactic Acid Bacteria with Cholesterol-Lowering Activity from Digestive Tracts of Indonesian Native Chickens - H. Julendra; Ade Erma Suryani; Lusty Istiqomah; Ema Damayanti; Muslih Anwar; Naditya Fitriani (Faculty of Animal Science, Bogor Agricultural University, 2017)
The aim of the study was to identify the cholesterol-lowering activity of indigenous lactic acid bacteria isolated from the small intestine, cecum, and colon of Indonesian native chickens and evaluated for bile salt hydrolase (BSH) activity in vitro by using MRS media added taurodeoxycholic acid (TDCA) and CaCl2. The quantitative measurement of cholesterol-lowering activity of LAB was investigated by using soluble cholesterol containing MRS broth (100 µg/mL of cholesterin) and incubated at 37 °C for 48 h. Cholesterol content in supernatant was analyzed using microplate reader. The highest percentage of cholesterol reduction found in isolates from colon of native chicken with the value of 17.43% and identified as Lactobacillus plantarum. Based on phylogenetic tree analysis, this isolate was closely related to L. plantarum strain LGFCP4 (accession number KM199683.1) isolated from GIT of Guinea fowl from India. It could be concluded that L. plantarum AKK-30 had cholesterol-lowering activity.